Effect of Mangosteen Pericarp Meal and Vitamin E Supplements on the Performance, Blood Profiles, Antioxidant Enzyme and HSP 70 Gene Expression of Laying Hens in Tropical Environment - Rusli, R.K.; Wiryawan, K.G.; Toharmat, T.; Jakaria; Mutia , R. (International Journal of Poultry Science, 2015)
This research aims to study the effects of mangosteen pericarp meal (MPM) and vitamin E (VE) on the performance, blood profile, antioxidant enzyme and HSP 70 gene expression of laying hens in tropical environment when supplemented in their diets. In this study, 160 laying hens of Lohman strains were used; they were 24 weeks old and were observed for 11 weeks. They were arranged in a completely randomized design with four treatments and four replications (10 birds each). The treatments consisted of R0 (control diet), R1 (R0+1 g MPM/kg rations), R2 (R0+2 g MPM/kg rations) and R3 (R0+200 mg VE/kg rations). The data were analyzed using analysis of Variance (ANOVA); if there was any significant difference among the treatments, further tested was done using Duncan Multiple Range Test. The results showed that supplementation of MPM and VE in the diet of the hens significantly (p<0.01) increased the activity of the antioxidant enzyme superoxide dismutase (SOD) and decreased the thiobarbituric acid reactive substances (TBARS) values. Supplementing the hens’ diet with MPM and VE did not affect (p>0.05) their performance, blood profile and HSP70 gene expression. It is concluded that supplementing the diets of the laying hens with MPM and VE increased the activity of SOD and decreased TBARS values of yolk.